Potential of Hexadecanoic Acid as Antimicrobials in Bacteria and Fungi that Cause Decay in Mustard Greens Brassica juncea L. - Nadhila Idris (Hasanuddin University, 2022)
Mustard greens Brassica juncea L. one of vegetable that is very easily damaged by microorganisms known as soft rot disease. This causes a decrease in the quality of green mustard so that it cannot last long. A study entitled “The Potential of Hexadecanoic Acid Compounds as Antimicrobials in Bacteria and Fungi that Cause Decay in Mustard Greens Brassica juncea L.